World Politics in Early 21st Century: Theoretical Forecasts and Contemporary Trends - Sergey A. Lantsov; Irina S. Lantsova (Сравнительная политика)
The article compares the forecasts concerning trends in world politics of the early 21st century created by Francis Fukuyama, Samuel Huntington and Immanuel Wallerstein. Though none of the forecasts was completely accurate, all of them spoke of the tendencies that could be later observed in world politics. Despite many experts criticized Fukuyama’s concept of the ‘end of history’, Western elites had been making foreign policies of their countries in accordance with the concept until recently.The article explains how such policies came to contradict contemporary state of affairs. In accordance with Huntington’s expectations, the role of civilizational factor in world politics of the early 21st century signifi cantly grew compared to previous periods. However, the character of civilizational factor’s infl uence on political processes appeared to be different compared to what Huntington expected. The article underlines the accuracy of Wallerstein’s forecast concerning the consequences of mass South-North migration. At the same time, the article concludes, his forecast, likewise the other two, also requires adaptation to contemporary situation in societal development.